THE EXEMPLARY LIFE OF BABUR MIRZA IN THE INTERPRETATION OF STEPHEN MEREDITH (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article examines the hard life and unique work of Zahiriddin Muhammad Babur on the basis of the prominent writer Stephen Meredith and his outstanding work, “Babur: the Diarist and the Despot”. The interpretation of Babur as a great king and commander, an unparalleled writer and poet, a true expert in the fields of art, gardening and construction has been analyzed with various life examples.